KRITIK SOSIAL VERSI MASYARAKAT KELAS BAWAH DALAM KELAKAR PANCE KARYA HENDRA ALFANI - Erlinda Rosita (Kibas Cenderawasih : Jurnal Ilmiah Kebahasaan dan Kesastraan, 2019)
The presence of satirical column in the form of rubric of Malay language, Ogan dialect, in OKU Express, Baturaja, Ogan Komering Ulu regency, South Sumatera as the background of this research. The column is titled “Kelakar Pance” by Hendra Alfani. The social criticism discussed is a form of critical thinking lower class society at Baturaja, Sumatera Selatan. The issues discussed the social criticusm in lower class society. The aim of this study is to describe the kind of social criticism versus the lower class society. The method of text analysis by collecty the data is used, that is, note and the inventory with objective approach. The object of the study is “Belulok” and “Susun Dinces”. The theory of dialectic Burger and Luckmaan is used. The result of the study in “Beluluk” is the lerk of the goverment attention to ward preservation of the enau trees. Which result the price of enau fruit is expensive. The control of the enau trees is reduced. In the text of “Susun Dinces”, the criticism is about amount of angdes is not comparable with the amount of passanger, as a result the passanger comfort is not priority.